PERAN MANAJERIAL KEPALA SEKOLAH DALAM MANAJEMEN SEKOLAH DI SDN 172 ENREKANG KECAMATAN ENREKANG KABUPATEN ENREKANG - Suhardiman, Andi (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2016)
The formulation of Problems are: 1) How the Role of Head Master in school Management of Elementary School of 172 Enrekang. 2) What Problems are faced by The Head Master in School Management. 3) Some factors that support the school management in Elementary School of 172 EnrekangThe objective of the research is to analyze the role of Head master in managing the Elementary School of 172 Enrekang, including: Planning, actuating and supervising.The research is qualitative research by using some informants as a source of the data. the research is done by interview methods, observations, documentations. The data is analyzed by using descriptive quantitative methods based on planning, actuating and supervising. So it can be concluded that School Management in Elementary School of 172 Enrekang has been done but not too maximal yet. This is because there are still many problems, specially on fee, teachers (dominated by women). However there are some internal potentials supporting, according to the Head Master, such as (1) Human Resources, (2) Environment. Human resource has important role to increase the development of the school; The number of staffs, The qualification of the staffs, and the skill of the staffs. Beside that, Elementary school of 172 Enrekang has had some professional and qualification teachers in supporting the teaching and learning process. Finally, Elementary School of 172 Enrekang supported by external institutions such as Educational institution, Religion institution, Healthy institution and School Comitee.